Influenza Effects in the Community - Davitadze, Sophiko; Ateş, Ateş; Çapkın, Semagül (Turkey Health Literacy Journal, 2021)
Influenza is a disease of varying severity, characterized by respiratory tract involvement, involving the chest, bronchi and rarely the lung, caused by the RNA virus from the Orthomyxoviridae family. In influenza, whose symptoms are similar to seasonal flu, sudden onset of high fever, headache, sore throat, runny nose, widespread muscle aches in the body, fatigue, weakness, tremors and non-productive cough are predominant. Diarrhea and vomiting may also accompany the symptoms. The virus creates viruses in different genomes and causing new infections to occur, undergoing frequent changes thanks to the segments of its RNA encoding different proteins thus leading to various epidemics and pandemics. For influenza virus, which has two surface glycoproteins, Hemagglutinin (H) and Neuraminidase (NA), which determine the antigenicity and pathogenicity of the virus, these glycoproteins are important in determining the virus types. Influenza viruses have A, B and C main types according to nucleocapsid and matrix proteins. Thanks to its segmented genome structure, it has many subtypes with recombination and modification of sub-antigens.Although influenza causes disease in all age groups, certain groups are affected more. The elderly, those with chronic diseases, those with immunodeficiency, etc. is a group developing complications and mortality risk is high.Morbidity and mortality rates are high in this group. Complications develop with the addition of bacterial infections secondary to influenza.
Keywords: Influenza, pandemic influenza, seasonal influenza, influenza in the community, influenza complications, prevention and treatment.